A proposal of assessment for generic competences in Engineering degrees - María Martínez Martínez; Beatriz Amante García; Ana Cadenato Matía; Rosa Rodríguez Montañés (Universitat Politècnica de València, 2013)
During the year 2011-12 a compulsory second-year course named Project I has been given, for the first time, in all engineering degrees offered at the School of Industrial Engineering of Barcelona at the Universitat Politècnica de Catalunya. This course has been designed with the aim of introducing students to engineering projects by consolidating and applying previously acquired knowledge and it becomes, at the same time, a key subject because of representing the first contact between students and generic competencies. Among the seven generic comptencies designed as compulsory by the university, effective communication, teamwork and autonomous learning have been the selected ones to be achieved through this subject at a first level (out of three levels). In order to conver the demand of this subject 12 projects assigned to different departments were offered and designed for hosting groups of 18 to 20 students.One or two lecturers tutored each group. The assessment system and the assesment criteria were common to all projects, so that 80% of the grading was the same for all the members of each group and was distributed along the course in 3 different deliverables, while the remaining 20% resulted in individual marks. This paper presents the strategy and tools that have been used for the assessment that has been carried out in the project developed within the area of Chemical Engineering entitled "what is the difference between the water we drink and water from rivers and seas?: composition, characterization and pollutings. The results show that using objective assessment tools and involving students in the assessment process facilitates the gradual acquisition of generic competencies as well as the specific competencies of the scope of the project.